A link between inflammation and metastasis: serum amyloid A1 and A3 induce metastasis, and are targets of metastasis-inducing S100A4 - Hansen, Matilde Thye; Sleeman, Jonathan P. (Oncogene, 2015)
S100A4 is implicated in metastasis and chronic inflammation, but its function remains uncertain. Here we establish an S100A4-dependent link between inflammation and metastatic tumor progression. We found that the acute-phase response proteins serum amyloid A (SAA) 1 and SAA3 are transcriptional targets of S100A4 via Toll-like receptor 4 (TLR4)/nuclear factor-κB signaling. SAA proteins stimulated the transcription of RANTES (regulated upon activation normal T-cell expressed and presumably secreted), G-CSF (granulocyte-colony-stimulating factor) and MMP2 (matrix metalloproteinase 2), MMP3, MMP9 and MMP13. We have also shown for the first time that SAA stimulate their own transcription as well as that of proinflammatory S100A8 and S100A9 proteins. Moreover, they strongly enhanced tumor cell adhesion to fibronectin, and stimulated migration and invasion of human and mouse tumor cells. Intravenously injected S100A4 protein induced expression of SAA proteins and cytokines in an organ-specific manner. In a breast cancer animal model, ectopic expression of SAA1 or SAA3 in tumor cells potently promoted widespread metastasis formation accompanied by a massive infiltration of immune cells. Furthermore, coordinate expression of S100A4 and SAA in tumor samples from colorectal carcinoma patients significantly correlated with reduced overall survival. These data show that SAA proteins are effectors for the metastasis-promoting functions of S100A4, and serve as a link between inflammation and tumor progression.